"Mental health is not our core business": A qualitative study of mental health supports in the Ghanaian mining industry. (January 2022) - Asare-Doku, Winifred; James, Carole; Rich, Jane Louise; Amponsah-Tawiah, Kwesi; Kelly, Brian
Highlights: Mental health policies are needed to guide practice. Understanding the local context when developing mental health interventions is key. Employees should be actively engaged in their own mental health literacy. Management support is essential in employee mental health. Abstract: Background: There is growing recognition of mental health aspects of workplace health and safety. Mining is a significant enterprise in the African continent; however, limited attention has been given to mental health in mining in this region. Ghana is the largest gold producer in Africa and mining contributes significantly to the economy. Mental health problems can have significant implications for the wellbeing and safety of mining employees, yet little is known about this in diverse geographic and cultural contexts. This study aims to explore mental health and available supports from the perspective of managers in mining companies in Ghana. Methods: A qualitative descriptive methodology was used to collect in-depth information from managers of international mining companies in Ghana. After receiving institutional ethics approval, all managers from the five mine sites were invited to participate in an interview. All interviews were audiotaped and transcribed verbatim for thematic analysis. Results: Three major themes were identified: Health Promotion, which explored health assessments and health promotion onsite activities; Onsite Support which included policy, human resources and medical supports; thirdly External Support, examined formal and informal supports such as family and social networks. Conclusion: Mental health was implied in various activities undertaken at the mine rather than being specific to targeting mental health directly. This study demonstrates the absence of mental health supports in mining in Ghana. Efforts should be made to incorporate mental health programs within the general health and safety policy, and an understanding of the local social norms and culture is vital.